PEACEFUL COEXISTEUCE THROUGH THE SUNNAH OF THE PROPHET (PEOPLE OF KETAAB AS A MODEL) (Islamic Sciences Journal, 2023)
This research deals with an aspect of the hadith sciences, especially peaceful coexistence, through which within Islam the rights of the individual to live comfortably in Islamic society, which is based on justice and equality among its members, whether the individual is Muslim or non-Muslim. Coexistence with the other does not mean absolutely dissolving it and the loss of Muslim identity, but rather means mutual respect and knowledge of each individual's wealth of rights and duties and that its goal is to know the Prophet’s guidance in treating Muslims and others in all areas of life. And highlighting the advantages of the teachings of the Prophet (Peace be Upon Him) over other religions.
Keywords: peaceful coexisteuce , people of book, guidance of the prophet, Justice, equality.